Taxonomy and phylogenetic relationships of Cyrtodactylus (Squamata: Gekkonidae) in Vietnam - Thi Hanh, Ngo; Duc Minh, Le; Duy Nghia, Pham; Thi Hong Van, Nguyen; The Cuong, Pham; Quang Truong, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 1SDO - 10.25073/2588-1140/vnunst.4530, 2017)
Cyrtodactylus is one of the most diverse genera of the family Gekkonidae in Vietnam. The species number of this genus has remarkably increased from three in 1997 to 38 at present. Due to their morphological similarity, the taxonomy of bent-toed geckos is unclear. Based on recently collected samples from 24 provinces in Vietnam we conducted a range-wide investigation of the phylogenetic relationships for the Vietnamese species using a fragment of the COI mitochondrial DNA gene. Our analyses showed that C. paradoxus is a junior synonym of C. condorensis and that C. thuongae is a junior synonym of C. dati . Our results also recovered four distinct clades of the genus Cyrtodactylus in Việt Nam: the clade A containing C. hontreensis, C. intermedius , C. cf. phuquocensis ; the clade B consisting of C. badenensis, C. bidoupimontis, C. bugiamapensis, C. caovansungi, C. cattienensis, C. cryptus, C. cucdongensis, C. dati, C. eisemanni, C. grismer, C. huynhi, C. irregularis, C. kingsadai, C. leegrismer, C. paradoxus, C. phuocbinhensis, C. pseudoquadrivirgatus, C. takouensis, C. taynguyenensis, C. yangbayensis and C. ziegleri ; the clade C containing C. phongnhakebangensis, C. roesleri ; and the clade D consisting of remaining species.